Clinical characteristics and gene analysis of GRIN2B gene related neurological developmental disorders in children - Tian, X J (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2022)
Objective: To analyse the clinical and gene characteristics of GRIN2B gene related neurological developmental disorders in children. Methods: The data of 11 children with GRIN2B gene related neurological developmental disorders from November 2016 to February 2021 were collected from Department of Neurology, Beijing Children's Hospital, Capital Medical University, National Center for Children's Health and analyzed retrospectively. The clinical features, electroencephalogram (EEG), brain imaging and gene testing results were summarized. Results: Among 11 children 6 were boys and 5 were girls. Two of them were diagnosed with developmental and epileptic encephalopathy. The ages of seizures onset were 3 months and 9 months, respectively. Seizure types included epileptic spasm, tonic seizures, tonic spasm and focal seizures, and 1 patient also had startle attacks. EEG showed interictal multifocal epileptiform discharges. Both of them were added with more than 2 anti-seizure drugs, which were partially effective but could not control. They had moderate to severe mental and motor retardation. The phenotype of 9 cases was developmental delay or intellectual disability without epilepsy, age of visit 1 year to 6 year and 4 months of whom 5 cases had severe developmental delay, 2 cases had moderate and 2 cases had mild delay. Multi-focal epileptiform discharges were observed in 3 cases, no abnormality was found in 3 cases, and the remaining 3 cases did not undergo EEG examination. Ten cases underwent brain magnetic resonance imaging (MRI), 6 cases had nonspecific abnormalities and 4 cases were normal. Nine GRIN2B gene heterozygous variants were detected by next-generation sequencing in these 11 patients, 8 cases had missense variants and 1 case had nonsense variant, all of which were de novo and 3 of which were novel. Missense variants were found in 10 patients, among them 6 cases had severe developmental delay, 3 cases had moderate and 1 case had mild developmental delay, but the patient with nonsense variant showed mild developmental delay without epilepsy. Conclusions: The phenotypes of GRIN2B gene related neurological developmental disorders in children are diverse, ranging from mild intellectual impairment without epilepsy to severe epileptic encephalopathy. Patients with epileptic phenotype usually have an onset age of infancy, and spasm and focal seizures are the most common seizure types. And the epiletice episodes are refractory. Most of the patients with missense variants had severe developmental delay